Pengaruh Lifestyle, Convenience Value, dan Perceived Risk terhadap Purchase Intention Pada E-Commerce Shopee - Jeany Aurieal Liberty Carandy; Syahputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increasing number of internet users has had an impact on businesses to innovate in their business activities. This innovation begins with the emergence of various online shopping platforms such as Shopee, Bukalapak, Tokopedia, etc. In the competitive business world, marketers can analyze the buying interests of the public to predict what products they should sell. This research was conducted to determine the extent of the influence of lifestyle, convenience value, and perceived risk on purchase intention on the Shopee e-commerce platform. Questionnaire distribution and quantitative data analysis were used to obtain data. The sample collection process utilized non-probability sampling, resulting in a total of 390 respondents. The analysis methods in this study involved multiple regression analysis tests, and the analysis program was operated using SPSS 29. From the simultaneous and partial hypothesis testing conducted, it was found that lifestyle, convenience value, and perceived risk significantly influence both simultaneously and partially on purchase intention on Shopee e-commerce, amounting to 59,3%. The remaining 40,7% was influenced by other unexamined variables not discussed in this study. The conclusion of this research is that the influence of lifestyle, convenience value, and perceived risk on purchase intention on Shopee e-commerce already in. the good category, but some improvements are needed, such as periodic updates and being more proactive in paying attention to sellers who do not provide detailed product explanations.